Stepwise Detection of Copy Number Variations in Whole Genome Sequence of Buffalo - Dash, Aishwarya; Sivalingam, Jayakumar; Bidyalaxmi, Kangabam; M, Kousalya Devi; Sukhija, Nidhi; D, Ravi Kumar; Niranjan, Saket Kumar; Tantia, Madhu Sudan; Gupta, Ishwar Dayal (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Genetic variants cause changes in genetic composition and are accountable for uniqueness of genomes of individuals. Copy number variations (CNVs) cause genetic variations due to loss or gain of DNA segments varying from 50 bp to several mega base pairs (Mb) compared with a reference genome. These unbalanced structural variants are heritable and have potentially greater effect than SNPs. The present study was conducted on whole genome resequencing (WGS) data of swamp buffalo for identification of CNVs. Sample of swamp buffalo was collected from Manipur and karyotyped and confirmed to be of swamp type. After quality and quantity checking it was sent for sequencing with Illumina Hiseq 2000 platform. Paired end reads of WGS data were analysed using Read depth (RD) based approach aligning to the reference Mediterranean riverine buffalo assembly. CNVs were identified using CNVnator with standardized parameters and total 587 CNVs were found in swamp buffalo. Among CNV events, 405 deletions and 182 duplications were identified. These variations comprised of 5.82% of reference genome. This was the first Genome-wide CNV study in indigenous swamp buffalo with reference to buffalo genome using Read Depth based approach.
Keywords: Buffalo; Copy number variations (CNVs); Read Depth; Whole genome sequencing (WGS)